A cell-based smoothed finite element formulation for viscoelastic laminated composite plates considering hygrothermal effects. (June 2021) - Nguyen, Sy-Ngoc; Truong, Tam T; Cho, Maenghyo; Trung, Nguyen-Thoi
In the present study, the viscoelastic analysis is investigated for composite laminated plates using a smoothed finite element method called cell/element based smoothed discrete shear gap method. Moreover, the hygrothermal effects is considered on the viscoelastic responses of composite laminated plates. The first-order shear deformation theory is employed due to its simplicity and accuracy. With the help of the convolution theorem in Laplace transformation, the complex stress-strain relationship in integral form is simplified to linear in transformed domain. Therefore, all computing procedures are performed in the transformed domain and then, using inverse techniques (Fast Fourier Transform) to converted back to the real-time domain. The study provides an effective computational tool to analyze the viscoelastic response of laminated composite taking into account the influence of the time and hygrothermal effects.